The Value of the Beriuk Tinjal Tradition as a Strengthening of Student Character in the Global Era - Hanapi, Hanapi (Lembaga Bale Literasi, 2024)
The tradition of beriuk tinjal of the Sasak Lombok ethnic community reflects relevant social values, solidarity, care, and responsibility to strengthen the character of students in the global era. This research aims to explore the values contained in the tradition of beriuk tinjal at SMA Negeri 1 Selong and its impact on strengthening students' character. The research method uses a qualitative approach with a phenomenological type, data is collected through observations, interviews, and documents involving teachers, students, and community leaders. The data analysis technique uses the Miles and Huberman interactive model. The results of the study show that the values of the beriuk tinjal tradition have been integrated through learning activities, extracurriculars, and social projects. As a result, students show increased cooperation, social concern, and appreciation for culture while strengthening students' character rooted in local values.